Intra-generational Mobility and Repeated Cross-Sections : A Three-country Validation Exercise - Cruces, Guillermo (2012)
This paper validates a recently proposed method to estimate intra-generational mobility through repeated cross-sectional surveys. The technique allows the creation of a "synthetic panel" -- done by predicting future or past household income using a set of simple modeling and error structure assumptions -- and thus permits the estimation of lower and upper bounds on directional mobility measures. The authors validate the approach in three different settings where good panel data also exist (Chile, Nicaragua, and Peru). In doing so, they also carry out a number of refinements to the validation procedure. The results are broadly encouraging: the methodology performs well in all three settings, especially in cases where richer model specifications can be estimated. The technique does equally well in predicting short and long-term mobility patterns and is robust to a broad set of additional "stress" and sensitivity tests. Overall, the paper lends support to the application of this approach to settings where panel data are absent.